KETAHANAN KARIR DAN KETERAMPILAN KERJA DI KALANGAN PEKERJA GENERASI Z DI ERA DIGITAL - K. M. Faisal Reza; M. Fakhriansyah; Syamsul Falaq (Berajah Journal, 2026)
The rapid development of digital technology has brought significant changes to the world of work, especially for Generation Z workers who grew up and developed in a digital environment. Amidst the dynamics of the job market characterized by technological disruption, work flexibility, and career uncertainty, career resilience has become a critical competency that determines the sustainability and adaptability of individuals in the world of work. In addition, work skills, both technical and non-technical, play a strategic role in supporting Generation Z's ability to survive, adapt, and thrive in the digital era. This study aims to analyze the relationship between career resilience and work skills among Generation Z workers, as well as to identify the role of digital skills and soft skills in strengthening their career resilience. The research method used a quantitative approach with a survey technique of Generation Z workers active in various digital-based industrial sectors. Data were analyzed using descriptive and inferential statistical analysis to test the relationship between research variables. The results show that work skills, particularly digital skills, adaptability, problem-solving, and continuous learning, have a positive and significant influence on the career resilience of Generation Z workers. These findings emphasize the importance of developing work skills relevant to the demands of the digital era as a primary foundation in building career resilience among the younger generation. This research is expected to provide theoretical contributions to the development of career resilience studies as well as practical implications for organizations, educators, and policy makers in designing sustainable human resource development strategies.